Interspecies transmission of Rotaviruses among ruminants, dogs and humans: Current facts and remarks - VALIAKOS, G.; CHATZOPOULOS, D. C.; TSOKANA, C. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Rotaviruses are considered to be a major cause of diarrhoea to humans as well as a wide variety of animals and may cause serious economic losses in livestock animals, especially swine and ruminants. This fact, along with the genetic diversity that characterizes members of the Rotavirus group, raised concerns regarding the potential of virus interspecies transmission among various species of animals and humans. Regarding the presence and the epidemiology of Rotaviruses in ruminants in association with closely related humans and dogs, research is limited and few data have been presented in recent years. In this review we present all the latest information regarding the distribution of genotypes of Rotavirus strains in ruminants, dogs and humans.